Position-Selective Metal Oxide Nanostructures using Atomic Thin Carbon Layer for Hydrogen Gas Sensors - Yu, Hak Ki (Journal of Sensor Science and Technology, 2020)
A hydrogen sensor was fabricated by utilizing a bundle of metal oxide nanostructures whose growth positions were selectively controlled by utilizing graphene, which is a carbon of atomic-unit thickness. To verify the reducing ability of graphene, it was confirmed that the multi-composition metal oxide V2O5 was converted into VO2 on the graphene surface. Because of the role of graphene as a reducing catalyst, it was confirmed that ZnO and MoO3 nanostructures were grown at high density only on the graphene surface. The fabricated gas sensor showed excellent sensitivity.
Keywords: Atomic carbon layer; Hydrogen sensors; Metal oxide; Position selective growth